Performance testing with JMeter 3 : enhance the performance of your web application - Erinle, Bayo (Packt Publishing, 2017)
A practical guide to help you undertand the ability of Apache jMeter to load and performance test various server types in a more efficient way. About This Book Use jMeter to create and run tests to improve the performance of your webpages and applications Learn to build a test plan for your websites and analyze the results Unleash the power of various features and changes introduced in Apache jMeter 3.0 Who This Book Is For This book is for software professionals who want to understand and improve the performance of their applications with Apache jMeter. What You Will Learn See why performance testing is necessary and learn how to set up JMeter Record and test with JMeter Handle various form inputs in JMeter and parse results during testing Manage user sessions in web applications in the context of a JMeter test Monitor JMeter results in real time Perform distributed testing with JMeter Get acquainted with helpful tips and best practices for working with JMeter In Detail JMeter is a Java application designed to load and test performance for web application. JMeter extends to improve the functioning of various other static and dynamic resources. This book is a great starting point to learn about JMeter. It covers the new features introduced with JMeter 3 and enables you to dive deep into the new techniques needed for measuring your website performance. The book starts with the basics of performance testing and guides you through recording your first test scenario, before diving deeper into JMeter. You will also learn how to configure JMeter and browsers to help record test plans. Moving on, you will learn how to capture form submission in JMeter, dive into managing sessions with JMeter and see how to leverage some of the components provided by JMeter to handle web application HTTP sessions. You will also learn how JMeter can help monitor tests in real-time. Further, you will go in depth into distributed testing and see how to leverage the capabilities of JMeter to accomplish this. You will get acquainted with some tips and best practices with regard to performance testing. By the end of the book, you will have learned how to take full advantage of the real power behind Apache JMeter. Style and approach The book is a practical guide starting with introducing the readers to the importance of automated testing. It will then be a beginner's journey from getting introduced to Apache jMeter to an in-detail discussion of more advanced features and pos...